Creative Brand Publicity of Ramayana 'Mom in Rice Cooker' - Frisky Freny Matahari; Amir Machmud; Muhammad Umar Al Faruqi (Graduate School of Communication Universitas Bakrie, 2025)
This article examines the effectiveness of the Ramayana branding program using the Creative Brand Publicity (CBP) approach through creative advertisements featuring a mother emerging from a rice cooker. The research method used is a case study with a descriptive-qualitative approach. Data collection methods include media, professional, digital, and scientific document searches. The study results indicate that CBP effectively increases brand awareness and engagement, with positive sentiment and active audience participation. This study provides important insights for other brands looking to increase visibility and audience engagement through the CBP strategy.